FEDERAL AGENCY IN THE HEARING OF PROVISIONAL RELEASE PROCEEDINGS IN CRIMINAL CASES - Surawan, Siriluk (Rangsit Journal of Law and Society, 2023)
The objective of this independent study is to study and investigate aspects such as the provisions and objectives of provisional release measures, with a specific focus on Articles 106 to 119 (bis). Moreover, it studies the intricacies and obstacles encountered in the practical implementation of provisional release measures concerning individuals accused of offenses or defendants entangled in criminal cases. In addition to this, the study extends its purview to investigate the legal frameworks existing in the United States and Canada, where provisional release measures have been effectively employed to address pertinent issues. This study has revealed that, notwithstanding the existence of provisional release measures in Thailand designed to provide equitable benefits to both financially disadvantaged and affluent defendants or accused offenders, the current judicial process faces a significant shortfall in the availability of requisite information for comprehensive deliberation. At this juncture, prevailing legal provisions empower the court to exercise its discretion in the evaluation of provisional release. If the court receives complete information about the defendant or accused offenders, it will result in a more impartial court decision, as observed in the United States and Canada, where the establishment of central agencies for provisional release has proven to be highly effective. Therefore, it is advisable to establish a Provisional Release Bureau, particularly with a structured format and operational procedures, based on the authority granted by the Royal Decree for the establishment of a central agency to facilitate the court's deliberation before granting provisional release on every occasion. The Provisional Release Bureau should conduct data investigation, assess flight risks, prepare reports, and provide recommendations to the court for deliberation before granting temporary release. Hence, it is advisable to establish a Federal Agency In The Hearing Of Provisional Release Proceedings In Criminal Cases, as stipulated by the Royal Decree, outlining its responsibilities and specific duties concerning the implementation of provisional release.